1989
DOI: 10.1038/sc.1989.35
|View full text |Cite
|
Sign up to set email alerts
|

Transition of physical fitness in wheelchair marathon competitors over several years

Abstract: SummaryTwenty eight stress tests for 14 wheelchair marathon competitors were performed to determine their physical fitness just before the Oita International wheelchair mara thon since 1984. All the subjects were wheelchair-bound Japanese males and workers at Sun Industry. Oxygen consumption at the maximal workload was significantly larger than that of non-athletic paraplegics and the mean values were 35·0 ± 4·8 ml/kg in competitors and 22·6 ± 5·0 ml/min/kg in non-athletic paraplegics. Eight competitors had mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…It has already been shown that from the first existence of an endurance event, it takes about one decade for elite able-bodied athletes to reach a more stable level of performance 25. There is no doubt that improvement in wheelchair technology and training methods during the 1980s and 1990s have contributed to the decrease in wheelchair marathon times since 1983 1015,26. Racing strategies such as drafting techniques (ie, cycling directly behind a competitor) may also help to improve performance 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been shown that from the first existence of an endurance event, it takes about one decade for elite able-bodied athletes to reach a more stable level of performance 25. There is no doubt that improvement in wheelchair technology and training methods during the 1980s and 1990s have contributed to the decrease in wheelchair marathon times since 1983 1015,26. Racing strategies such as drafting techniques (ie, cycling directly behind a competitor) may also help to improve performance 27…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to marathons in able-bodied runners,8,9 there is no available research data on the participation and performance trends in wheelchair marathon performance across the last three decades. Due to the increase in social interaction of people with disabilities and the improvements in material,1013 technique, and training over the past three decades,14,15 an increase in the participation and improvement in wheelchair marathon performances since the 1980s for both males and females could be envisaged.…”
Section: Introductionmentioning
confidence: 99%
“…While training and racing in a wheelchair marathon is rather individual, athletes playing basketball in a team have more social interactions which may help to better handle the situation of disability (Giacobbi et al, 2008). (Hooker & Wells, 1992) and individual training for wheelchair marathoners improves the competitors' physical fitness over several years (Okuma et al, 1989). Athletes with spinal cord injury can maintain their fitness for 20 years when they maintain their sports activities (Shiba et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Work by Nash et al 2007 demonstrated that many of the cardiovascular disease risk factors present in persons with SCI appear to be reversible with exercise. Increasing HDL levels and decreased serum, total cholesterol and LDL levels, [14][15][16][17][18] as well as improved VO 2 , cardiac output and stroke volume 19,20 are among the physiological improvements achieved via exercise. While changes in exercise are vital, so is the need for nutrition education.…”
Section: Introductionmentioning
confidence: 99%